Industrialisasi Pendidikan Tinggi - Zamroni, M. Imam (Unisia, 2016)
This article aims to describe that the commercialization and industrialization of state higher education are dilemma for government’s policy in the era of globalization. On one hand, industrialization increases education expenditures, so that the poor people cannot access it, and on the otherhand, it can deliver advantages in the form of welfare for civitas academica and several investors as conducted by developed countries. On the contrary, high education expenditures oppose ambition to realize the Education for All (EFA).